'Feminists for Media Rights': A Case Study in Television Activism. Issue 1 (2nd January 2020) - Kibler, M. Alison
Abstract : In 1977, Feminists for Media Rights, of central Pennsylvania, announced that it had achieved 'victory' by reaching an agreement with the largest television station in the area, WGAL. The agreement promised new programs for women, a women's advisory committee and a women's program director. This article offers a critical assessment of this 'victory'. It takes a long view of a challenge to a station's license, including negotiations, petitions, agreements and the implementation of agreements, not simply an isolated petition or agreement, to dispel notions of a singular victory or loss. On one hand, FMR was justifiably pleased with WGAL's concessions: the station would produce a program about the Lancaster Women's Center, which was founded by radical feminists in Lancaster and broadcast a new, weekly women's public affairs show. On the other hand, while FMR had sought to create a feminist space on television, the station ultimately offered not feminist control, but new 'women's' programming, which was often quite traditional. The negotiations between FMR and WGAL shows that the feminist FCC strategy, initiated by the National Organization for Women, was more radical than previous accounts allow: feminists used the 'petition to deny' as a legal tool for trying to establish a feminist space on television. The FCC strategy was not simply reformist.